"If We Can Feel Like We Have Purpose and We Belong" - Exploring the Experiences of Drug-Involved Individuals in a Rural Jail. Issue 4 (1st October 2020) - Keesler, John M.; Brault, Emily; Powell, Joshua; Johnston, Helen
ABSTRACT: In rural areas, drug-involved individuals are frequently incarcerated rather than engaged in treatment or rehabilitation. While jails contend with high rates of incarceration, surrounding communities struggle with a dearth of resources and risk factors for adversity. The current study explored the experiences and perspectives of 21 individuals (71% men) who were incarcerated for drug-related offenses in the rural Midwest. Structured interviews queried individuals' life experiences, outlook, and recommendations for the jail and the community. Interviews were analyzed using open coding and a constant comparative method. Eight codes emerged from the data and comprised three themes: preceding and concurrent challenges to sobriety ("familial dysfunction", "stigma", and "loss and fear"); moving toward a recovery mind-set ("gaining insight", "hopeful", and "motivation for change"); and, maintaining or challenging the status quo ("personal supports" and "environmental characteristics"). Amid pervasive adversity, individuals maintained a realistic perspective of their recovery. Despite their readiness for change, a lack of jail and community resources were perceived barriers to future success. The individuals demonstrated personal insight and made recommendations for systemic change. Although incarceration can provide time for treatment, interventions need to be available and consider a multi-systems perspective given the implications of family dynamics and community quality of life.